Guest Editorial: Doctoral Studies in Library and Information Science in India - Kumar, P.S.G. (DESIDOC Journal of Library & Information Technology, 2003)
Universities are demanding a doctoral degree for library and information science faculty as well as for professional seniors in university and other higher education and research libraries. This led to increased research activity at various iibrary schools in India. 'This paper provides statistics of doctoral research in India. The data of the doctoral research in India has been analysed chronobgically, subject-wise, guide-wise, and university-wise. http://dx.doi.org/10.14429/dbit.18.1.3381